Semi-steel dephosphorizing agent and semi-steel pre-dephosphorizing method

By using a semi-steel dephosphorizing agent composed of iron oxide scale and highly active lime, combined with nitrogen blowing and temperature control, the problems of corrosiveness and low efficiency of existing dephosphorizing agents have been solved, achieving a highly efficient, safe, and environmentally friendly semi-steel dephosphorization effect.

CN121450880APending Publication Date: 2026-02-03SICHUAN FANGDA VANADIUM & TITANIUM GROUP CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202511711868.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-11-20
Publication Date
2026-02-03

AI Technical Summary

Technical Problem

Existing dephosphorizing agents for semi-steel have problems such as strong corrosivity, easy deliquescence, complicated storage conditions, and low dephosphorization efficiency. In particular, lime-based dephosphorizing agents have slow slag formation, low reaction efficiency, and may cause environmental pollution.

Method used

A semi-steel dephosphorizing agent composed of iron oxide scale and highly active lime in a specific ratio is used. By controlling the ratio of FeO and CaO, low-melting-point calcium ferrite is generated, which improves the fluidity of the slag. The reaction is promoted by nitrogen blowing. Combined with precise control of temperature and addition time, efficient dephosphorization is achieved.

Benefits of technology

It achieves efficient, safe, and environmentally friendly dephosphorization of semi-steel, with a dephosphorization rate of 10-20%, reducing the dephosphorization load on the converter, shortening the smelting cycle, and eliminating environmental pollution and storage safety hazards.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention belongs to the technical field of semi-steel dephosphorization, and discloses a semi-steel dephosphorization agent and a semi-steel pre-dephosphorization method, the semi-steel dephosphorization agent is composed of oxide scale and lime according to the mass ratio of 1: (1.5-2.5), the FeO content of the oxide scale is larger than or equal to 50 wt%, the CaO content of the lime is larger than or equal to 85 wt%, and the activity degree is larger than 350 mL. The semi-steel pre-dephosphorizing method comprises the following steps: in the semi-steel tapping process of a converter, adding the semi-steel dephosphorizing agent into a semi-steel ladle according to the adding amount of 4.375 kg of oxide scale per ton of semi-steel, and introducing nitrogen for blowing after the semi-steel tapping is completed. The semisteel dephosphorizing agent provided by the invention is good in dephosphorizing effect, free of pollution to the environment, free of corrosion, easy to store and free of potential safety hazards and environmental pollution problems; meanwhile, the semi-steel pre-dephosphorization method is easy to operate, facilities and equipment do not need to be additionally built, the dephosphorization rate outside the converter can reach 10%-20%, the converter dephosphorization load is relieved, and the smelting period is shortened.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application belongs to the technical field of semi-steel dephosphorization, and particularly relates to a semi-steel dephosphorization agent and a semi-steel pre-dephosphorization method. BACKGROUND

[0002] Vanadium and titanium are contained in the molten iron obtained by smelting vanadium-titanium magnetite in a blast furnace, and the rare elements can be removed by a converter while vanadium is extracted, but phosphorus cannot be removed, so the semi-steel after the extraction of vanadium by the converter contains a high phosphorus content. Generally, phosphorus is a harmful element in most steel types, and the implementation of semi-steel pre-dephosphorization before converter steelmaking can reduce the dephosphorization load of converter smelting and realize the preparation of ultra-low phosphorus content steel.

[0003] The semi-steel pre-dephosphorization process is currently popular, which is to remove phosphorus in the semi-steel in the semi-steel ladle during the semi-steel process of the vanadium extraction converter. Patent CN103205536B discloses a semi-steel dephosphorization agent and a semi-steel dephosphorization method, which can effectively remove the phosphorus content in the semi-steel, and the dephosphorization rate can reach more than 40%. The semi-steel dephosphorization agent provided by the patent is made of 5-50 parts of lime, 25-45 parts of iron oxide scale and 22-25 parts of sodium oxide. Sodium oxide is an extremely efficient dephosphorization agent in semi-steel dephosphorization, and the slag has good fluidity, but it has strong corrosiveness and can quickly corrode the skin, metal and other materials. Direct contact with sodium oxide can cause serious consequences such as skin burns and eye damage, so the semi-steel dephosphorization agent provided by patent CN103205536B is dangerous when used, and sodium oxide is extremely easy to absorb moisture in the air, which causes itself to gradually deliquesce. This not only changes its chemical properties, but also may cause corrosion to the storage container, so the storage conditions of the semi-steel dephosphorization agent provided by patent CN103205536B are also relatively complex. SUMMARY

[0004] Therefore, the purpose of the present application is to provide a semi-steel dephosphorization agent that is easy to store and a semi-steel pre-dephosphorization method that is simple and safe to operate.

[0005] In order to achieve the above technical effects, the present application provides the following technical solutions.

[0006] Firstly, the present application provides a semi-steel dephosphorization agent, which is composed of iron oxide scale and lime in a mass ratio of 1:(1.5-2.5), the FeO content of the iron oxide scale is ≥50wt%, and the mass percentage of the particle size less than 5mm is 2-3%; the CaO content of the lime is ≥85wt%, the activity is >350mL, and the mass percentage of the particle size less than 5mm is 1.8-2.2%.

[0007] Further, in a preferred embodiment of the present application, the semi-steel dephosphorization agent is composed of iron oxide scale and lime in a mass ratio of 1:1.7.

[0008] Further, in a preferred embodiment of the present application, the FeO content of the iron scale is 51-52wt%, and the mass percentage of the particle size less than 5mm is 2.8-2.9%; the CaO content of the lime is 88-89wt%, the activity is ≥380 mL, and the mass percentage of the particle size less than 5mm is 1.9-2.0%.

[0009] Secondly, the present application provides a semi-steel pre-dephosphorization method, which comprises the following steps: Step 1, preparing the semi-steel dephosphorization agent described above; Step 2, during the semi-steel tapping process, the semi-steel dephosphorization agent of step 1 is added into the semi-steel ladle, and the addition amount of the semi-steel dephosphorization agent is controlled according to 4.375kg of iron scale per ton of semi-steel; Step 3, after the semi-steel tapping is completed, nitrogen gas is blown into the bottom of the semi-steel ladle to make the liquid surface in the semi-steel ladle slightly fluctuate; The semi-steel is a semi-steel with vanadium extracted by a converter, and the temperature is ≥1360℃.

[0010] Further, in a preferred embodiment of the present application, the temperature of the semi-steel is 1400-1450℃. Since the dephosphorization reaction is a strong exothermic reaction, a lower temperature is required, but too low a temperature is not conducive to the melting of lime and the fluidity of slag. The present application precisely controls the semi-steel temperature to ensure that the dephosphorization reaction proceeds efficiently and smoothly.

[0011] Further, in a preferred embodiment of the present application, the addition time of the semi-steel dephosphorization agent in step 2 is when there is 1 / 4 of the volume of the semi-steel ladle in the semi-steel ladle, the semi-steel dephosphorization agent is started to be added, and the addition of the semi-steel dephosphorization agent is completed before there are 2 / 3 of the volume of the semi-steel ladle in the semi-steel ladle. When there is 1 / 4 of the volume of the semi-steel ladle in the semi-steel ladle, the semi-steel dephosphorization agent of the present application is added into the semi-steel ladle through a downcomer, and the impact of the semi-steel molten steel promotes the reaction of the dephosphorization agent and the molten steel, thereby improving the dephosphorization efficiency.

[0012] Further, the blowing of nitrogen gas into the bottom of the semi-steel ladle can strengthen the stirring effect of the molten steel, promote the mixing of the slag and the molten steel, and improve the dephosphorization efficiency. In a preferred embodiment of the present application, the blowing time of nitrogen gas into the bottom of the semi-steel ladle in step 3 is 6-10min. Further, in a preferred embodiment of the present application, the blowing time of nitrogen gas into the bottom of the semi-steel ladle in step 3 is 8min.

[0013] Further, in a preferred embodiment of the present application, it further comprises step 4, after the blowing of nitrogen gas is completed, the liquid surface in the semi-steel ladle is subjected to slag skimming treatment. The slag skimming treatment can improve the purity of the molten steel and prevent “phosphorus return”.

[0014] Lime (CaO) based dephosphorization agent is the most widely used mainstream dephosphorization agent in the steel industry at present, but due to the high melting point of lime, it leads to slow slagging speed and low reaction efficiency, and the existing technology usually adds fluorite to improve fluidity and overcome the slow slagging defect, but the addition of fluorite will exacerbate the erosion of refractory materials, and may produce fluoride pollution in the production process, which is not friendly to the environment.

[0015] The iron oxide scale, commonly known as "iron scale", is a scale peeled off on the surface during rolling, and the main component is FeO. In the semi-steel dephosphorization reaction, the iron oxide scale provides an oxygen source (FeO) to oxidize P elements into P2O5, and lime provides an alkali source (CaO) to convert unstable P2O5 into stable compound tetra calcium phosphate (4CaO·P2O5), so as to permanently fix phosphorus in the steel slag and remove it.

[0016] Since FeO has a relatively low melting point (about 1370℃), it reacts with lime (CaO, melting point 2572℃) to generate low-melting-point calcium ferrite (such as CaO·Fe2O3, melting point about 1200℃), which helps to reduce the melting point of the slag body, improve fluidity, accelerate the melting and dissolution of lime, and promote the full contact and reaction between the dephosphorization agent and the molten iron. Moreover, the reduction of FeO by carbon, silicon and other elements in the molten iron (FeO + [C] → [Fe] + CO) is an endothermic reaction, which helps to offset the heat generated by the dephosphorization reaction and the oxidation of other elements, thereby controlling the temperature rise of the molten iron and creating more favorable low-temperature conditions for dephosphorization. The present application adjusts the mass ratio of iron oxide scale and lime, specifically the ratio of FeO and CaO, so that the amount of added iron oxide scale not only ensures the large removal of P elements in semi-steel, but also generates sufficient calcium ferrite to improve the fluidity of the slag body, while ensuring a certain amount of FeO to be reduced to control the temperature rise of the molten iron. Moreover, the present application selects high-activity lime for reaction, which can quickly react with semi-steel liquid in the semi-steel ladle compared with low-activity lime, quickly form slag, thereby improving the dephosphorization efficiency, and the slag generated by the reaction of high-activity lime is more uniform, delicate and has good fluidity, which can better cover the metal liquid surface and improve the reaction interface. Therefore, the semi-steel dephosphorization agent provided by the present application solves the problems of slow slagging speed and low reaction efficiency of lime (CaO) based dephosphorization agent, and does not add corrosive or environmentally polluting components, is easy to store and friendly to the environment.

[0017] In summary, compared with the prior art, the beneficial effects of the present application are: The semi-steel dephosphorization agent provided by the present application has good dephosphorization effect, is non-polluting to the environment, non-corrosive, easy to store, and has no safety hazards and environmental pollution problems; at the same time, the semi-steel pre-dephosphorization method provided by the present application is simple to operate, does not require additional facilities and equipment, can achieve a dephosphorization rate of 10-20% outside the furnace, and can reduce the dephosphorization load of the converter and speed up the smelting cycle. DETAILED DESCRIPTION

[0018] The technical solutions in the embodiments of the present application will be clearly and completely described below. Obviously, the described embodiments are only a part of the embodiments of the present application, rather than all the embodiments. Based on the embodiments in the present application, all the other embodiments obtained by a person of ordinary skill in the art without creative work fall within the protection scope of the present application.

[0019] The ingredient compositions of the millscale balls and active lime involved in the following embodiments are shown in Table 1 and Table 2.

[0020] Table 1. Ingredient composition table of millscale balls

[0021] Table 2. Ingredient composition table of active lime

[0022] Embodiment 1: The semi-steel in the semi-steel ladle for dephosphorization treatment weighed 80 tons. When there was 1 / 4 semi-steel ladle volume of semi-steel in the semi-steel ladle, 350 kg of millscale balls and 500 kg of active lime were added into the semi-steel ladle through a downcomer, and the addition was completed before there was 2 / 3 semi-steel ladle volume of semi-steel in the semi-steel ladle. After the semi-steel tapping was completed, nitrogen was blown into the bottom of the semi-steel ladle to make the liquid level in the semi-steel ladle slightly fluctuate. After the nitrogen blowing for 8 min, the P content was detected by sampling.

[0023] The P content of the semi-steel without dephosphorization treatment was 0.127 wt%, and the temperature was 1410℃. After the dephosphorization treatment, the P content was 0.118 wt%, and the temperature was 1362℃. The dephosphorization rate was 7%.

[0024] Embodiment 2: The semi-steel in the semi-steel ladle for dephosphorization treatment weighed 80 tons. When there was 1 / 4 semi-steel ladle volume of semi-steel in the semi-steel ladle, 350 kg of millscale balls and 500 kg of active lime were added into the semi-steel ladle through a downcomer, and the addition was completed before there was 2 / 3 semi-steel ladle volume of semi-steel in the semi-steel ladle. After the semi-steel tapping was completed, nitrogen was blown into the bottom of the semi-steel ladle to make the liquid level in the semi-steel ladle slightly fluctuate. After the nitrogen blowing for 8 min, the P content was detected by sampling.

[0025] The P content of the semi-steel without dephosphorization treatment was 0.139 wt%, and the temperature was 1420℃. After the dephosphorization treatment, the P content was 0.113 wt%, and the temperature was 1360℃. The dephosphorization rate was 18.7%.

[0026] Embodiment 3: The semi-steel weight in the semi-steel ladle is 80 tons, 350 kg of iron oxide scale balls and 700 kg of active lime are added into the semi-steel ladle through the discharging chute when the semi-steel in the semi-steel ladle is 1 / 4 of the volume of the semi-steel ladle, and the addition is completed before the semi-steel in the semi-steel ladle is 2 / 3 of the volume of the semi-steel ladle, and after the semi-steel tapping is completed, nitrogen is blown into the bottom of the semi-steel ladle to make the liquid level in the semi-steel ladle slightly fluctuate, and the P content is detected after 8 min of nitrogen blowing.

[0027] The P content of the semi-steel without dephosphorization treatment is 0.137 wt%, the temperature is 1405℃, the P content after dephosphorization treatment is 0.119 wt%, the temperature is 1352℃, and the dephosphorization rate is 13.1%.

[0028] Example 4: The semi-steel weight in the semi-steel ladle is 80 tons, 350 kg of iron oxide scale balls and 700 kg of active lime are added into the semi-steel ladle through the discharging chute when the semi-steel in the semi-steel ladle is 1 / 4 of the volume of the semi-steel ladle, and the addition is completed before the semi-steel in the semi-steel ladle is 2 / 3 of the volume of the semi-steel ladle, and after the semi-steel tapping is completed, nitrogen is blown into the bottom of the semi-steel ladle to make the liquid level in the semi-steel ladle slightly fluctuate, and the P content is detected after 8 min of nitrogen blowing.

[0029] The P content of the semi-steel without dephosphorization treatment is 0.135 wt%, the temperature is 1430℃, the P content after dephosphorization treatment is 0.116 wt%, the temperature is 1360℃, and the dephosphorization rate is 14.1%.

[0030] In summary, the semi-steel dephosphorization agent composed of iron oxide scale and lime in a mass ratio of 1:(1.5-2.5) provided by the application can achieve a dephosphorization rate of 10-20% outside the furnace, reduce the dephosphorization load of the converter and speed up the smelting cycle.

[0031] The above is only the preferred embodiment of the application, and it should be pointed out that the above preferred embodiment should not be regarded as a limitation of the application, and the protection scope of the application should be limited by the scope defined in the claims. For ordinary skilled persons in the art, several improvements and refinements can be made without departing from the spirit and scope of the application, and these improvements and refinements should also be regarded as the protection scope of the application.

Claims

1. A semi-steel dephosphorizing agent, characterized in that: The semi-steel dephosphorizing agent is composed of iron oxide scale and lime in a mass ratio of 1:(1.5-2.5). The iron oxide scale has an FeO content ≥50wt% and a particle size less than 5mm by mass percentage of 2-3%. The lime has a CaO content ≥85wt%, an activity >350mL, and a particle size less than 5mm by mass percentage of 1.8-2.2%.

2. The dephosphorizing agent for semi-steel according to claim 1, characterized in that: The semi-steel dephosphorizing agent is composed of iron oxide scale and lime in a mass ratio of 1:1.

7.

3. The dephosphorizing agent for semi-steel according to claim 1, characterized in that: The iron oxide scale has an FeO content of 51-52 wt% and a particle size of less than 5 mm by mass percentage of 2.8-2.9%; the lime has a CaO content of 88-89 wt%, an activity of ≥380 mL, and a particle size of less than 5 mm by mass percentage of 1.9-2.0%.

4. A method for pre-dephosphorizing semi-steel, characterized in that: Includes the following steps: Step 1: Prepare the semi-steel dephosphorizing agent according to any one of claims 1 to 3; Step 2: During the process of producing semi-steel from the converter, the semi-steel dephosphorizing agent from Step 1 is added to the semi-steel ladle. The amount of semi-steel dephosphorizing agent added is controlled at 4.375 kg of iron oxide scale / t of semi-steel. Step 3: After the semi-steel is tapped, nitrogen gas is introduced into the bottom of the semi-steel ladle to cause slight fluctuations in the liquid level inside the ladle. The semi-steel is vanadium-extracted semi-steel obtained by converter extraction at a temperature ≥1360℃.

5. The pre-dephosphorization method for semi-steel according to claim 4, characterized in that: The temperature of the semi-steel is 1400-1450℃.

6. The pre-dephosphorization method for semi-steel according to claim 4, characterized in that: In step 2, the dephosphorizing agent for the semi-steel is added when the semi-steel ladle contains 1 / 4 of its volume of semi-steel, and the addition is completed before the semi-steel ladle contains 2 / 3 of its volume of semi-steel.

7. The pre-dephosphorization method for semi-steel according to claim 4, characterized in that: In step 3, nitrogen gas is introduced into the bottom of the semi-steel ladle for 6 to 10 minutes.

8. The pre-dephosphorization method for semi-steel according to claim 6, characterized in that: In step 3, nitrogen gas is introduced into the bottom of the semi-steel ladle for 8 minutes.

9. The pre-dephosphorization method for semi-steel according to claim 4, characterized in that: Also includes: Step 4: After nitrogen purging is completed, remove slag from the liquid surface inside the semi-steel ladle.

Citation Information

Patent Citations

  • Dephosphorizing agent and method for semi-steel

    CN103205536B